2017
DOI: 10.1002/anie.201701306
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a Stable Amide into a Highly Reactive One: Capturing the Essence of Enzymatic Catalysis

Abstract: Aspartic proteinases, which include HIV-1 proteinase, function with two aspartate carboxy groups at the active site. This relationship has been modeled in a system possessing an otherwise unactivated amide positioned between two carboxy groups. The model amide is cleaved at an enzyme-like rate that renders the amide nonisolable at 35 °C and pH 4 owing to the joint presence of carboxy and carboxylate groups. A currently advanced theory attributing almost the entire catalytic power of enzymes to electrostatic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Although the TPP:Cu equilibrium formation constant is not significantly high, the catalytic effect is noteworthy, and this perfectly suits the use of anionic micelles of SDS as nanoreactors: approximation of the substrate and the metal ion within a confined environment through hydrophobic and electrostatic effects favors the formation of the TPP:Cu complex within the micellar environment, as evidenced by typical saturation kinetics. The results show a very special micellar effect, which combines the exploitation of some of the primary driving forces important for the efficiency of enzyme catalysis, such as approximation of the reactants by hydrophobic and electrostatic components, as well as by acid‐base complexation. The results can aid the planning of novel biomimetic systems with enhanced catalytic activity for the targeted detoxification of phosphotriesters …”
Section: Discussionmentioning
confidence: 99%
“…Although the TPP:Cu equilibrium formation constant is not significantly high, the catalytic effect is noteworthy, and this perfectly suits the use of anionic micelles of SDS as nanoreactors: approximation of the substrate and the metal ion within a confined environment through hydrophobic and electrostatic effects favors the formation of the TPP:Cu complex within the micellar environment, as evidenced by typical saturation kinetics. The results show a very special micellar effect, which combines the exploitation of some of the primary driving forces important for the efficiency of enzyme catalysis, such as approximation of the reactants by hydrophobic and electrostatic components, as well as by acid‐base complexation. The results can aid the planning of novel biomimetic systems with enhanced catalytic activity for the targeted detoxification of phosphotriesters …”
Section: Discussionmentioning
confidence: 99%
“…The study of the mechanism of reactions is key to understand chemical transformations requiring careful experimental design including solvent effect, reaction regioselectivity and stereospecificity . Nucleophilic aromatic substitution (S N Ar) reactions have been widely applied in industrial processes, being studied since the 19th century .…”
Section: Introductionmentioning
confidence: 99%
“…Although intramolecular catalysis is efficient and frequently observed in enzyme catalysis and in biomimetic models which include the reactions of amides and carboxylic and phosphate esters, it is less explored in synthetic preparations. In this regard, it has been shown that N ‐acetylaminoacids can be conveniently prepared using aspirin as the acetylating agent of amino acids in aqueous medium .…”
Section: Introductionmentioning
confidence: 99%